2018
DOI: 10.1016/j.abb.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Optical assessment of skin carotenoid status as a biomarker of vegetable and fruit intake

Abstract: Resonance Raman spectroscopy (RRS) and reflection spectroscopy (RS) are optical methods applicable to the non-invasive detection of carotenoids in human skin. RRS is the older, more thoroughly validated method, whereas RS is newer and has several advantages. Since collective skin carotenoid levels serve as a biomarker for vegetable and fruit intake, both methods hold promise as convenient screening tools for assessment of dietary interventions and correlations between skin carotenoids and health and disease ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 30 publications
2
105
1
Order By: Relevance
“…Compared with the small number of other studies that have used the Veggie Meter™ technique, our mean CRS value of 346 is higher than that recorded in a diverse community sample in Eastern North Carolina USA of~240 in African American and Non-African American (n = 469) [21] and 57 from an eye clinic in Utah, USA [14] with mean CRS of 297, but similar to a Japanese study where the mean CRS was 342 [15]. While we show no significant difference in CRS between men and women, the Japanese [15] study demonstrated that Japanese women scored higher than men (382 vs. 315).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Compared with the small number of other studies that have used the Veggie Meter™ technique, our mean CRS value of 346 is higher than that recorded in a diverse community sample in Eastern North Carolina USA of~240 in African American and Non-African American (n = 469) [21] and 57 from an eye clinic in Utah, USA [14] with mean CRS of 297, but similar to a Japanese study where the mean CRS was 342 [15]. While we show no significant difference in CRS between men and women, the Japanese [15] study demonstrated that Japanese women scored higher than men (382 vs. 315).…”
Section: Discussioncontrasting
confidence: 69%
“…This relatively rapid measurement, less than 15 s, enables immediate feedback and interpretation of the measurement to the individual. The device has been used to evaluate carotenoid reflection scores (CRS) of participants in the United States of America [14] and Japan [15] but not in New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure‐mediated reflection spectroscopy (RS) is an improved method (over RRS) to measure skin carotenoid status and is highly correlated with RRS‐assessed skin carotenoids ( 13 ) . The Veggie Meter® is a portable RS device and, unlike the RRS device, it is available for purchase.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, skin carotenoids measured with pressuremediated re ection spectroscopy is a validated method to approximate FV intake. [27][28][29] In this paper, we explored associations between self-reported and objectively-measured FV intake and three measures of farmers' market shopping behavior: (1) monthly frequency of farmers' market shopping, (2) variety of FV purchased on one market day, and (3) money and/or bene ts typically spent on FV at the farmers' market per week, in both a rural population and a racially/ethnically diverse urban population. We hypothesized that FV intake, measured both by self-report and skin carotenoids, would be positively associated with shopping frequency at farmers' markets, variety of FV purchased, and money and/or bene ts spent on FV.…”
Section: Introductionmentioning
confidence: 99%